Pain management in trauma: the need for trauma-informed opioid prescribing guidelines - Ben L Zarzaur; Suresh Agarwal,; Colleen Trevino; Amelia Baltes; David M Horton; Julia Malicki; Randall T Brown (Trauma Surgery & Acute Care Open)
Background/objectives Surgical populations and particularly injury survivors often present with complex trauma that elevates their risk for prolonged opioid use and misuse. Changes in opioid prescribing guidelines during the past several years have yielded mixed results for pain management after trauma, with a limiting factor being the heterogeneity of clinical populations and treatment needs in individuals receiving opioids. The present analysis illuminates this gap between clinical guidelines and clinical practice through qualitative feedback from hospital trauma providers and unit staff members regarding current opioid prescribing guidelines and practices in the setting of traumatic injury.Methods The parent study aimed to implement a pilot screening tool for opioid misuse in four level I and II trauma hospitals throughout Wisconsin. As part of the parent study, focus groups were conducted at each study site to explore the facilitators and barriers of implementing a novel screening tool, as well as to examine the current opioid prescribing guidelines, trainings, and resources available for trauma and acute care providers. Focus group transcripts were independently coded and analyzed using a modified grounded theory approach to identify themes related to the facilitators and barriers of opioid prescribing guidelines in trauma and acute care.Results Three major themes were identified as impactful to opioid-related prescribing and care provided in the setting of traumatic injury; these include (1) acute treatment strategies; (2) patient interactions surrounding pain management; and (3) the multifactorial nature of trauma on pain management approaches.Conclusion Providers and staff at four Wisconsin trauma centers called for trauma-specific opioid prescribing guidelines in the setting of trauma and acute care. The ubiquitous prescription of opioids and challenges in long-term pain management in these settings necessitate additional community-integrated research to inform development of federal guidelines.Level of evidence Therapeutic/care management, level V.